1989
DOI: 10.1093/oxfordjournals.jbchem.a122971
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Fatty Acids with β-Lactoglobulin and Albumin from Ruminant Milk1

Abstract: beta-Lactoglobulin isolated from milk of cow, sheep, and goat had about 0.5 mol of fatty acids bound per mol of monomer protein. Fatty acids, mainly palmitic and oleic acids, were the major components (about 75% of total lipids). Albumin isolated from the same samples had about 4.5 mol of fatty acids bound per mol of protein. These two proteins were the only whey proteins able to bind labeled fatty acids in vitro. Interaction of beta-lactoglobulin and albumin with insolubilized fatty acids showed some differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 0 publications
7
75
0
1
Order By: Relevance
“…The binding site in ␤-Lg is rather fully extended, but there is space for longer fatty acid molecules such as stearate and oleate to be accommodated within the calyx, with the carboxyl group making the same interactions with Lys-60 and Lys-69. The association constants for both acids are similar (33,34). In the fatty acid-binding protein family, palmitate is also observed in an extended form, although alternative conformations of bound fatty acids have been observed (35,36).…”
Section: Complex Of Palmitate With ␤-Lactoglobulinmentioning
confidence: 85%
“…The binding site in ␤-Lg is rather fully extended, but there is space for longer fatty acid molecules such as stearate and oleate to be accommodated within the calyx, with the carboxyl group making the same interactions with Lys-60 and Lys-69. The association constants for both acids are similar (33,34). In the fatty acid-binding protein family, palmitate is also observed in an extended form, although alternative conformations of bound fatty acids have been observed (35,36).…”
Section: Complex Of Palmitate With ␤-Lactoglobulinmentioning
confidence: 85%
“…1 and references therein). ␤-Lactoglobulins isolated from cow, goat, and sheep milk samples, under nondenaturing conditions, showed endogenously bound fatty acids (2). Many authors have suggested that bovine ␤-lactoglobulin (BLG) 1 has a transport and/or protective role toward bound ligands in the stomach (3).…”
mentioning
confidence: 99%
“…Therefore, either beneficial or detrimental changes can be produced as a result of high-pressure treatment [52]. 4.2 Effects of high hydrostatic pressure on functional properties of β-LG β-LG binds fatty acids in vivo [53] and a large variety of hydrophobic ligands in vitro [54], such as retinol, sodium dodecyl sulphate [55], and aroma compounds [56]. β-LG is known to interact with many flavor compounds, such as aldehydes, ketones [57], ionones [58], and hydrocarbons [59].…”
Section: Pressure-induced Changes In Protein Structurementioning
confidence: 99%